2021
DOI: 10.1017/ice.2021.135
|View full text |Cite
|
Sign up to set email alerts
|

Sustained reduction in catheter-associated urinary tract infections using multi-faceted strategies led by champions: A quality improvement initiative

Abstract: We reviewed the sustainability of a multifaceted intervention on catheter-associated urinary tract infection (CAUTI) in 3 intensive care units. During the 4-year postintervention period, we observed reductions in urine culture rates (from 80.9 to 47.5 per 1,000 patient days; P < .01), catheter utilization (from 0.68 to 0.58; P < .01), and CAUTI incidence rates (from 1.7 to 0.8 per 1,000 patient days; P = .16).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…140146 Involve local champions to promote the program. 137,139,145,147,148 Utilize peer networking. 66,144,148,149 Involve patient and family. …”
Section: Section 6: Implementation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…140146 Involve local champions to promote the program. 137,139,145,147,148 Utilize peer networking. 66,144,148,149 Involve patient and family. …”
Section: Section 6: Implementation Strategiesmentioning
confidence: 99%
“…Inappropriate uses of catheters remained low during follow-up and did not appear to be affected by the intervention. 136 Similarly, Reynolds et al 137 described a multifaceted CAUTI prevention initiative led by physician and nurse champions in ICUs at Duke University Hospital. The investigators observed a sustained reduction in rates of urine-culture utilization, catheter utilization, and CAUTI over 4 years.…”
Section: Section 6: Implementation Strategiesmentioning
confidence: 99%